(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The increasing prevalence of smartphone usage among adolescents has raised concerns about its impact on postural health. This study explores the association between smartphone use, ergonomic habits, and body mass index (BMI) with postural abnormalities in adolescents. Methods: A cross-sectional study was conducted involving 200 adolescents aged 13–18 years. Data were collected through a structured questionnaire assessing smartphone usage patterns, ergonomic habits, and demographic information. BMI was calculated using height and weight measurements, and postural abnormalities were assessed using a standardized observational checklist. Chi-square tests and logistic regression analyses were performed to identify significant associations and risk factors. Results: Prolonged smartphone use (>4 hours/day) was significantly associated with postural abnormalities (p=0.015, OR=2.15, 95% CI: 1.30–3.55). Poor ergonomic habits, such as lying down while using a smartphone or maintaining prolonged neck flexion, also showed a strong association with postural abnormalities (p=0.001, OR=3.50, 95% CI: 2.00–6.10). BMI exhibited a weak but significant relationship (p=0.047, OR=1.75, 95% CI: 1.05–2.90). Gender and age group were not significantly associated with postural abnormalities. Conclusion: This study highlights the significant impact of prolonged smartphone use and poor ergonomic habits on adolescent posture. BMI also contributes to postural abnormalities, albeit to a lesser extent. These findings emphasize the need for targeted interventions, including ergonomic education and behavioral modifications, to mitigate the risk of musculoskeletal disorders among adolescents. Further research is needed to explore these associations in larger and more diverse populations.